Sali de paseo - Williams, Sue, 1948-; Vivas, Julie, 1947- (New York : Harcourt, Brace and Co., 1989)
During the course of a walk, a young boy identifies animals of different colors.
Keywords: Walking -- Juvenile fiction; Color -- Juvenile fiction; Animals -- Juvenile fiction; Spanish language materials -- Juvenile fiction; Stories in rhyme -- Juvenile fiction